The Ingredients of Healthy Brain and Child Development - Pat Levitt; Kathie L. Eagleson (Washington University Journal of Law & Policy, 2018)
This article by Pat Levitt and Kathie L. Eagleson explains critical developmental stages in early childhood and adolescent brain development. Levitt and Eagleson start by dispelling certain misconceptions about early brain development and then examining the interaction between biological events, social and emotional development, and the role played by early childhood experiences in healthy brain development. Finally, the article discusses the importance of intervention programs on healthy brain development and positive child, adolescent, and adult outcomes.
Keywords: prenatal; postnatal; adolescent; brain development; cognition; cognitive development; intellectual disability; epigenetics; serve and return; executive function; socioeconomic status; Abecedarian preschool project; maturation; intervention programs; neuroscience